From “transitions” to “trajectories”: towards a holistic interactionistic analysis of educational inequality in contemporary China - Xiangyang Bi; Xueling Liu (Humanities & Social Sciences Communications, 2024)
Abstract This study employs sequence analysis to explore the educational pathways of individuals born in China between 1976 and 1988, a cohort that witnessed substantial educational expansion. The study constructs a typology for classifying these educational trajectories and quantifies the prevalence of each category within the cohort. Utilizing decision tree analysis, the study investigates the relationship between different educational pathways and various background characteristics. Unlike the “waning coefficients” commonly observed in Mare model and its variants, this approach unveils the substantial influence of cumulative advantage and disadvantage in shaping educational trajectories, a process heavily impacted by individuals’ social backgrounds. Despite some exceptions and complexities, several discernible patterns become apparent. For instance, individuals hailing from rural settings generally exhibit a decreased likelihood of progressing along superior educational trajectories throughout their academic endeavors when juxtaposed with their urban counterparts. Moreover, elevated levels of parental education persistently enhance children’s prospects for accessing superior educational pathways, irrespective of their urban or rural origins. This methodology serves as a valuable instrument for scrutinizing the general features and diversity of educational trajectories, providing a complementary perspective to existing research on educational stratification and inequality.